The European insurance industry: A PEST analysis - Charmaine Barbara; Dominic Cortis; Roberta Perotti; Claudia Sammut; Antoine Vella (International Journal of Financial Studies, 2017)
The insurance industry plays an important role for European economic stability and the threats and opportunities it faces should be carefully determined. In this paper we highlight the main challenges by using a Political, Economic, Social and Technological (PEST) analysis. This work applies conventional actuarial thought on this area by focusing strictly on the European sector.
Keywords: G10; G22; O16; 330; insurance; PEST; political; risks; challenges; economy; European Union